Effective immobilization of candida cylindracea lipase on surfactant-modified bentonite. Issue 1 (24th March 2023) - Meng, Zihao; Wu, Jian; Li, Qingyun; Liu, Youyan; Tang, Aixing
Abstract: Lipase OF from Candida cylindracea was adsorbed onto surfactant-modified Na-bentonite (Bent), and the effects of the surfactants on the catalytic properties of immobilized lipase were studied in detail. The results showed that both the specific activity and enzyme loading of immobilized lipase varied significantly with modified support of different surfactants. The highest specific activity was obtained with Tween20-modified Bent: 11.9-fold higher than the non-modified sample. Upon modification by a single surfactant, two kinds of surfactants were combined to process the modification. It was surprising to find that the enzyme immobilized on CTAB (60%) and TX-100 (40%) co-modified Bent yielded a specific activity recovery of 133.4% indicating that the enzyme might be "activated". Kinetic analyses for the hydrolysis of p-nitrophenyl palmitate ( p -NPP) showed that K m decreased from 5.57 mg mL −1 of free lipase to 3.43 mg·mL −1 and V max increased 1.35-fold higher. The structure, surface morphology, and hydrophobicity of the modified bentonite and immobilize lipase were characterized via X-ray diffraction, Fourier transform-infrared spectroscopy, scanning electron microscopy, and contact angle measurements. We assumed that lipase molecules may be bound to the surface of the carrier, and the surface hydrophobicity and the change of the functional group caused by the modification of surfactant may be the key factor affecting lipase immobilization.